ANALISIS KEBIJAKAN PENATAAN RUANG DAN DUKUNGAN PARTISIPASI MASYARAKAT TERHADAP KELESTARIAN LINGKUNGAN (Suatu Studi Kasus di Kota Bekasi) - Djaelani, Moh. Solikodin (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2011)
The research is purpose to find out implementation spatial planning policies on Bekasi city for stainable environmental management? Analytical methods used are: 1) Geo-physics analysis of land suitability analysis, 2) physical analysis; 3) Analysis of environmental management, 4) Analysis of socio-economic conditions, and 5) Analysis Geographic Information System (GIS). The results obtained that spatial planning and environmental carrying capacity can be concluded that to meet the needs of diverse development needs to develop a spatial pattern of land use, coordinate, procedures for water and other resources in a unified a dynamic environment. To meet the needs of diverse development needs to develop a spatial pattern coordinate system guana land, procedures for water and other resources in a unified order dynamic environment. For that layout needs to be managed by an integrated pattern through a regional approach with respect to site natural environment, socio-cultural environment, and the artificial environment in accordance with its development. Good city spatial structure with more increased public participation in city layout is expected to be better. The parties involved in these activities the city department of administration, the whole society. There is a direct influence on the city hall community participation in maintaining a healthy environment, so if you want to increase public participation in maintaining a healthy environment can be done by increasing the city spatial planning. Knowledge to community environmental management in maintaining a healthy environment, can be done by improving environmental management Knowledge community. The implementation of spatial management that take by the government in accordance with the spatial planning and its implementation has been set well and need to optimize. In the spatial implementation among others include: planning the provision and utilization of green open space, and plan the provision and utilization of network infrastructure and pedestrian facilities. Keywords: Analisys of Wisdom, lay out, participation society